1970
DOI: 10.1111/j.1476-5381.1970.tb12905.x
|View full text |Cite
|
Sign up to set email alerts
|

The release of acetylcholine by acetylcholine in the cat's superior cervical ganglion

Abstract: Summary1 The experiments described in this paper tested the effect of acetylcholine (ACh), carbachol or preganglionic nerve stimulation on the release of ACh from the cat's perfused superior cervical ganglion; radioactive tracer methods were used. 2. When the ganglion's transmitter store of ACh had been labelled, radioactive ACh was released by nerve stimulation (5 Hz for 2 min), but there was no release by ACh (015-15 jg) or by carbachol (1-10 Mig) when these drugs were injected close to the ganglion. Perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…The previous demonstration (Collier & Katz, 1970) (Brown & Feldberg, 1936;Feldberg, 1943) and it was assumed that 85% of the total ACh was releasable (Birks & MacIntosh, 1961;Collier & MacIntosh, 1969 Time ( The effect of acetylcholine-blocking agents upon the release of surplus acetylcholine induced by acetylcholine or by nicotine…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous demonstration (Collier & Katz, 1970) (Brown & Feldberg, 1936;Feldberg, 1943) and it was assumed that 85% of the total ACh was releasable (Birks & MacIntosh, 1961;Collier & MacIntosh, 1969 Time ( The effect of acetylcholine-blocking agents upon the release of surplus acetylcholine induced by acetylcholine or by nicotine…”
Section: Resultsmentioning
confidence: 99%
“…Two experiments showed that hexamethanium (2 x 1O-4M) clearly reduced the release of ACh induced by nicotine (Figure 5a). Five experiments tested whether hexamethonium (2 x 1 0-4 M) blocked the release of surplus ACh induced by ACh; in four of these release was almost completely abolished ( Figure Sb) (Brown et al, 1970;Collier & Katz, 1970 Kuhar & Simon, 1974 (Barker, Dowdall, Essman & Whittaker, 1970;Richter & Marchbanks, 1971;Marchbanks & Israel, 1971 The results of experiments which measured the uptake of exogenous ACh by ganglia that had, or had not, first accumulated surplus ACh were consistent with the conclusion that surplus ACh release by ACh does not result from ACh exchange. If the exchange occurred, it might be expected that accumulation of exogenous ACh would have been greater in ganglia with surplus ACh.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collier & Katz (1970) have shown that acetylcholine itself may also act to release quantities of surplus endogenous acetylcholine, although they believe that the presynaptic effects of acetylcholine are not of physiological importance.…”
Section: Introductionmentioning
confidence: 99%